Treatment with insulin is associated with worse outcome in patients with chronic heart failure and diabetes. (28th February 2018) - Cosmi, Franco; Shen, Li; Magnoli, Michela; Abraham, William T.; Anand, Inder S.; Cleland, John G.; Cohn, Jay N.; Cosmi, Deborah; De Berardis, Giorgia; Dickstein, Kenneth; Franzosi, Maria Grazia; Gullestad, Lars; et al.
Abstract : Aims: Up to one‐third of patients with diabetes mellitus and heart failure (HF) are treated with insulin. As insulin causes sodium retention and hypoglycaemia, its use might be associated with worse outcomes. Methods and results: We examined two datasets: 24 012 patients with HF from four large randomized trials and an administrative database of 4 million individuals, 103 857 of whom with HF. In the former, survival was examined using Cox proportional hazards models adjusted for baseline variables and separately for propensity scores. Fine–Gray competing risk regression models were used to assess the risk of hospitalization for HF. For the latter, a case–control nested within a population‐based cohort study was conducted with propensity score. Prevalence of diabetes mellitus at study entry ranged from 25.5% to 29.5% across trials. Insulin alone or in combination with oral hypoglycaemic drugs was prescribed at randomization to 24.4% to 34.5% of the patients with diabetes. The rates of death from any cause and hospitalization for HF were higher in patients with vs. without diabetes, and highest of all in patients prescribed insulin [propensity score pooled hazard ratio for all‐cause mortality 1.27 (1.16–1.38), for HF hospitalization 1.23 (1.13–1.33)]. In the administrative registry, insulin prescription was associated with a higher risk of all‐cause death [odds ratio (OR) 2.02, 95% confidence interval (CI) 1.87–2.19] and rehospitalization for HF (OR 1.42, 95% CI 1.32–1.53). Conclusions: Whether insulin use is associated with poor outcomes in HF should be investigated further with controlled trials, as should the possibility that there may be safer alternative glucose‐lowering treatments for patients with HF and type 2 diabetes mellitus.